Cross Talk between H2O2 and Interacting Signal Molecules under Plant Stress Response - Saxena, Ina; Srikanth, Sandhya; Chen, Zhong (Frontiers in Plant Science, 2016)
It is well established that oxidative stress is an important cause of cellular damage. During stress condition plants have evolved regulatory mechanism to adapt to various environmental stresses. One of the consequences of stress is an increase in the cellular concentration of ROS, which is subsequently converted to H2O2. H2O2 is continuously produced as the by-product of oxidative plant aerobic metabolism. Organelles with a high oxidizing metabolic activity or with an intense rate of electron flow, such as chloroplasts, mitochondria, or peroxisomes are major sources of H2O2 production. H2O2 acts as a versatile molecule because of its dual role in cells. Under normal conditions, H2O2 acts as a key regulator of many biological processes because H2O2 has been identified as an important second messenger in signal transduction networks. In this review we discuss potential roles of H2O2 and other signaling molecule during various stress responses.